The Roles of Band Bending, Surface Misorientation, and Passivation on Electrical Transport Across III-V Bonded Structures. (24th August 2016) - Yee, Matthew; Liao, Michael; Seal, Mark; Goorsky, Mark S.
Abstract : With results from bonding of several different materials combinations, surface orientations, and passivation treatments, as well as an assessment of barrier heights reported in the literature for transport in polycrystalline III-V materials as well as for other III-V bonded materials combinations, a general model has emerged. Lattice mismatch does not play a major role in limiting conductivity across an interface; however, misalignment (through twist or tilt) produces interfaces with increased resistance. Passivation techniques are most important for these systems which possess significant interface band-bending. The electrical characteristics of a grain boundary, whether in polcrystalline material or at a bonded interface, are determined by the presence of defect states and interfacial charge which create band bending and Fermi level pinning. The barrier heights and widths from zero bias conductance vs bias measurements over a wide range of temperatures and for different materials can be matched to band structure simulations of bonded semiconductor heterojunctions with resultant I-V curves showing good agreement between experiment and theory. Based on this study, which combines experimental results and transport modelling, it is expected that narrow bandgap III-V semiconductors should show lower barrier heights; but more importantly, modelling indicates that high doping at mismatched interfaces helps to significantly reduce the interface barrier height.